Drivers of Public Welfare Land Ratios for Regional Development in China: A Central–Local Interaction Perspective - Jin Dai; Qingbin Wang; Xiongwei Zhou; Xinxian Qi (Land)
Public welfare land allocation in China’s land expropriation process plays a crucial role in balancing economic development with social equity, but limited research has examined the driving factors influencing public welfare land ratio determination from a central–local relationship perspective. This study investigates how central–local government interactions shape public welfare land ratios in China’s land development process. Based on a comprehensive analysis of land expropriation data across different regions and administrative levels, we examine the spatial heterogeneity and underlying mechanisms of public welfare land allocation. The results reveal the following: (1) Significant regional variations exist for regional public welfare land ratios, with the national average public welfare land ratio reaching 41.21% in 2019 (for plots ≥4 hectares), varying from 39.60% in eastern regions to 44.93% in western regions. (2) Administrative hierarchy influences allocation patterns, with county-level cities (43.73%) showing higher proportions than provincial capitals (36.42%). (3) Local governments strategically use public welfare land development as an instrument to expand land-based fiscal resources by attracting investments and population. (4) Provincial governments serve as crucial intermediaries in central–local policy implementation, balancing central mandates with local conditions. This study contributes to the land governance literature by providing empirical evidence on how institutional arrangements affect land resource allocation. The findings suggest that establishing unified national standards while allowing provincial-level adaptations would improve the effectiveness of public welfare land policy in the post-land finance era, enhancing both governance efficiency and public welfare outcomes.